Academic Motivation as a key to success? An Attempt at Understanding Based on Perception: Academic Motivation as a key to success? An Attempt at Understanding Based on Perception (Simbiótica. Revista Eletrônica, 2024)
The following research seeks to describe Portuguese higher education students’ perspective on the role of motivation in academic performance, as well as what factors influence that motivation. To fulfill the objectives proposed, it was used a combined methodology: a quantitative method was used through the application of a survey to a sample of 158 Higher Education students, as well as a qualitative methodology through 9 semi-structured interviews. An overlook at the results indicates that the sampled higher education students see motivation as a simple work facilitator and that their motivation arises, essentially from extrinsic factors, although there is a recognition that they feel satisfaction in learning new subjects, their attendance in University is essentially compelled by favorable future life perspectives.